Pengaruh Pemberian Pupuk Kandang Sapi dan Jarak Tanam yang Berbeda terhadap Pertumbuhan Rumput Gajah Varietas Pakchong (Pennisetum purpureum cv. pakchong) (Jurnal Peternakan Lingkungan Tropis, 2023)
Pakchong elephant grass (Pennisetum purpureum cv. pakchong) is a forage fodder that is currently being intensively cultivated in cattle farming, fattening and nurseries, so it has the potential to be developed. Increased production of Pakchong Elephant Grass can be done by applying manure with proper fertilization and spacing. The experiment used a factorial Randomized Block Design (RAK) with 4 treatments and 3 replications. Parameters observed were plant height, leaf width, number of leaves, leaf length, dry weight balance of leaves and stems. The application of cow manure manure at a dose of 72 kg plot1 had a better effect, better spacing of 80 x 150 cm/treatment There was an interaction between the application of cow manure and plant spacing on the growth and production of Pennisetum purpureum cv. Pakchong. Fertilizer application of 72 kg plot-1 and spacing of 80 x 150 cm gave the best results.
Keywords: Array; Array; Array